Activation of lesion projection zone in primary visual cortex is dependent on bilateral central vision loss in patients with end‐stage glaucoma. (31st August 2022) - Zhu, Wenqing; Liu, Tingting; Li, Mengwei; Sun, Xinghuai; He, Sheng
Abstract: Purpose: To investigate activation of the lesion projection zone (LPZ) in the primary visual cortex during end‐stage glaucoma using functional magnetic resonance imaging (fMRI), as well as the relationship between fMRI responses and clinical data. Methods: Twelve subjects with bilateral end‐stage glaucoma (group A), 12 with unilateral end‐stage glaucoma (group B) and 12 healthy controls (group C) were enrolled. fMRI was performed under two testing stimuli conditions: passive viewing of a full‐field flickering checkerboard and active viewing of a one‐back task with scene images. In fMRI analysis, the primary visual cortex was divided into six regions of interest (ROIs). The beta values of the six ROIs were compared across the three groups using one‐way analysis of variance under two viewing conditions. Associations between the fMRI beta value and clinical data including multifocal electroretinogram (mfERG), microperimeter‐1 and optical coherence tomography were analysed by Spearman correlation. Results: The beta values for ROIs 1–3 representing the LPZ were significantly different between the three groups under active viewing conditions, whereas no significant changes were detected under passive viewing. In group A, there were significant differences between all six ROIs for the two viewing conditions, while no significant differences were found in groups B and C. In group A, the P‐wave amplitudes of the mfERG was significantly correlated with the beta values of ROIs 1 and 2 under active viewing. In addition, the P‐wave latencies of the mfERG were significantly correlated with the beta values for ROIs 2–5. No associations were found between fMRI beta values and clinical data in groups B and C. Conclusions: Activation of the LPZ in the primary visual cortex was observed in patients with bilateral end‐stage glaucoma under active viewing conditions. These changes were correlated with residual retinal function.